Interleukin-10 blocks atherosclerotic events in vitro and in vivo - Pinderski Oslund, L J; Hedrick, C C; Olvera, T; Hagenbaugh, A; Territo, M; Berliner, J A; Fyfe, A I (Arteriosclerosis, thrombosis, and vascular biology, 1999)
Atherosclerosis can be viewed in part as an inflammatory disease process and may therefore be susceptible to manipulation of the immune state. Interleukin 10 (IL-10) is an inhibitory cytokine produced by activated lymphocytes and monocytes. These studies present evidence that IL-10 can inhibit minimally oxidized LDL (MM-LDL)-induced monocyte-endothelium interaction as well as inhibit atherosclerotic lesion formation in mice fed an atherosclerotic diet. Pretreatment of human aortic endothelial cells (HAECs) for 18, but not 4, hours with recombinant IL-10 caused a significant decrease in MM-LDL-induced monocyte binding. IL-10 was found to be maximally effective at 10 ng/mL. Transfection of HAECs with adenovirus expressing viral bcrf-1 IL-10 (Ad-vIL-10) in a sense but not antisense orientation completely inhibited the ability of MM-LDL to induce monocyte binding. Similar results were obtained with IL-10 or Ad-vIL-10 in HAECs stimulated with oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine (OxPAPC). We have previously shown increases in cAMP associated with MM-LDL activation of endothelial cells. The MM-LDL-induced increase in cAMP levels was not inhibited by preincubation with IL-10. In vivo studies demonstrated that mice with a murine IL-10 transgene under the control of the human IL-2 promoter have decreased lesions versus controls on an atherogenic diet (5433+/-4008 mm(2) versus 13 574+/-4212 mm(2); P<0.05), whereas IL-10 null mice have increased lesions (33 250+/-9117 mm(2); P<0.0001) compared with either controls or IL-10 transgenic mice. These studies suggest an important role for IL-10 in the atherosclerotic disease process.